PENGEMBANGAN MULTIMEDIA INTERAKTIF MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA MATA PELEJARAN IPA KELAS VIII SMP KATOLIK KEMBES - Cliver Rafael Kindangen; Meike Paat; Ni Wayan Suryani; Jovialine A Rungkat (SOSCIED, 2023)
The purpose of this study is to develop and determine the feasibility of interactive multimedia using the Problem Based Learning (PBL) model in grade VIII science subjects of Kembes Catholic Junior High School. This type of research is Research and Development (R&D) research. The development model used is the Borg & Gall model adapted by Sugiyono. Data collection techniques use observation, interview, and questionnaire techniques. Based on validation trials, material experts and media experts obtained excellent criteria and are suitable for use in the field. Then small group trials also obtained very good criteria.